Control interno en el área de inventario y su impacto en la rentabilidad de la empresa “El Hermano Sandro” Cantón Quevedo Provincia De Los Ríos, año 2022. - Cuzme Sánchez, Erika Estefani (2023)
The elaboration of the current investigation aims to develop an Internal Control Model in the inventory area to establish its impact in the company “El Hermano Sandro” in Quevedo canton, period 2022. The authors used inductive, deductive, and analytical methods. The types of research were: applied, field, and qualitative research. To diagnose the current situation in the company's inventory area, the internal control questionnaire COSO I was applied, based on the components of Control Environment, Risk Assessment, Control Activities, Information and Communication, and Supervision. The application of the COSO I questionnaire reflects that the level of confidence calculated in a consolidated manner corresponds to all the components of the internal control questionnaire COSO I, evidencing 90%, and placing it in a HIGH range, while the level of the calculated risk was 10%, situating it in a LOW range. Finally, the researchers designed an internal control model as their proposal for the inventory area of the company “El Hermano Sandro”. To conclude, the company does not have internal control procedures in the inventory area, for this reason the proposal highly recommended.